Analysis of the Magnetic Anomalies of Buried Archaeological Ovens of Aïn Kerouach (Morocco) - Abderrahim Ayad; Saâd Bakkali (International Journal of Geophysics)
Aïn Kerouach is one of the most important archaeological sites in the northern part of Morocco. The main buried archaeological ruins in this area were surveyed in 1977 using magnetic prospecting. This survey highlights the mean anomalies that are related to potteries ovens built to the Marinid dynasty that governed Morocco from the 13th to the 15th century. In order to find the maximum depth of the sources, we computed the enhanced downward continuation filter in order to highlight the magnetization contrasts in high detail, depending on the depth downward included in the computation. The main goal is providing a reliable mapping to observe the ovens in depth by shifting the data below the plane of measurement. The results showed an important depth variation of the main ovens given by the original magnetic map and revealed others. Indeed, the downward continuation process applied to analyze the magnetic data shows its efficiency to highlight the buried archaeological structures.